(untitled) (Baghdad Science Journal, 2019)
The quality of groundwater should be improved by keeping safe water sources from contaminants in protective way by doing regular measuring and checkup before it supplied for usage. Private Wells do not receive the same services that wells supplying the public do. Well owners are responsible for protecting their drinking water. This work was carried out in Badra city, Iraq from December 2017 to May 2018, six wells water were investigated to determine the general characteristics of wells as well as studying the effect of environmental factors on the quality of water. The average of six wells were eleven parameters that is out of permissible limits were EC, Sal., Alk., TH, TDS, Na, Ca, Cl, SO4, Fe, Zn (4402-5183 /cm, 2.76-3.9 ppt, 302-366mg/L, 3164-4248 mg/L, 604-675 mg/L, 375-524 mg/L, 635-871 mg/L, 631-1107 mg/L, 2430-4570 g/L, 114-392 g/L). Respectively, microbiological investigations involved the total coliform, total plate count, as well as the detection for the presence of E. coli, Salmonella and Cholera. Results shows that there is a significant relation between the increasing of the TDS and Turbidity, TDS gives an indication for the significant increasing of chemical ions. Wells number 3, 4 and 5 showed gave positive results for E.coli growth which as a source of microbial pollution. Detection for the presence of chemical and microbial contaminate is an important alarm since this water has a direct effect on the human and animal’s health. Advance method of rapid detection for the well water quality is highly recommended to avoid any health issue and prevent the outbreak of health risk and ecological contaminants.